Shaping the Future: A Research Agenda for U.K. Libraries - Tilley, Elizabeth; Marshall, David (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2024)
Objective – This study explored current and future trends in librarianship within the U.K. library and information profession, intending to highlight the most critical for future evidence based research. Research outcomes should resonate across the wider sector and be an indicative stepping stone to collaborative research endeavours by members of the profession at a time when funding is tight, and staff availability is in short supply.Methods – A qualitative Delphi consensus method was chosen for the research, adapted from Paul’s (2008) modified Delphi card-sorting model. Contributions from conference programs and 31 individual experts from the U.K. library and information profession contributed to the generation of current themes and trends impacting their library environments. Data were analyzed by the experts in an incremental manner following the adapted methodology, and consensus was achieved through the process.Results – The findings of the research indicated that there were five significant trends and areas of concern which are impacting our libraries at all levels. These naturally include pressing current concerns such as the impact of artificial intelligence (AI), critical librarianship, and censorship/book banning. Library spaces remain a significant issue for the wider sector.Conclusion – The adapted modified Delphi card-sorting method with three distinct sections to the research proved especially valuable in a study where there were many different approaches to librarianship. The use of conference data to seed the initial set of themes has been shown to be unusual and rarely used in this way before. The process of achieving and reaching consensus illustrated the need for the profession as a whole to work more closely together. The outcome of the consensus research should now be taken forward collaboratively by the library profession, with space and training given to staff across all sectors and grades to engage in evidence based research for the benefit of all.